Paternity Test Through Kinship Analysis as Forensic Identification Technique - Ahmad Yudianto; Fery Setiawan; Reni Sumino (Majalah Kedokteran Bandung, 2021)
Paternity tests is often faced with the unavailability of information from the father, mother, or child as a comparison in forensic DNA examination process. Therefore, comparisons with information from close family lines are needed, for example from the victim's siblings or the perpetrator if there are no comparisons from parents or siblings. This study was conducted by the Human Genetic Study Group of Airlangga University in its campus from January to April 2020. The aim of the study was to analyze the use of kinship analysis in paternity test through STR CODIS examination on siblings. This was an observational laboratory study with a temporary design. DNA sample extraction level and purity results were measured with the mean DNA sample level of 675±5.35ng/µL, while the purity values ranged from 1.05 to 1.86. The paternity test principle is based on comparison process between the parents’ alleles with the child’s alleles. However, if the parents’ alleles are not available, the siblings’ alleles can be used as a comparison for identification purpose, which is known as kinship analysis. Statistically, full siblings have a 2 alleles accuracy probability of [0.25] 25%, which was the same as not having the same allele or 0 allele, while 1 allele accuracy reached 50%. All CODIS STR loci had the highest percentage of 2 allele sharing. Therefore, it is recommended to use sibling or kinship analysis if both parents are absent.